BUFFALO MEAT AS A HEALTHY FOOD - Rusdy, Muhammad (Proceeding Buffalo International Conference, 2013)
Proteins from animal sources are higher biological value than from plant sources, because animal proteins contain amino acids that more similar to our bodyâs need, however animal meats often contain high levels of saturated fats and cholesterol that increase the risk of heart disease. Differ to many land animals that contain high levels of saturated fatty acids, buffalo meat contains less saturated fatty acids, cholesterol and calories but higher in iron, vitamin B12 and protein than those of beef, pig Â and skinless chicken. Grass-fed animals contain higher omega-3 fatty acid, lower ratio of omega-6 and omega-3 and higher content of conjugated linoleic acid (CLA) than those of grain-fed animals.Â